Applicability of a Novel Attunement Instrument and Its Relationship to Parental Sensitivity in Infants With and Without Visual Impairments - Vacaru, Victorita Stefania; Alfaro, Andrea Urqueta; Hoffman, Nadia; Wittich, Walter; Stern, Micky; Zar, Heather J.; Stein, Dan J.; Sterkenburg, Paula Sophia (Frontiers in Psychology, 2022)
This study investigated the applicability of a novel instrument to assess parent-child attunement in free play interactions, in dyads with an infant with and without visual impairments (VI). We here report the findings on the reliability and applicability of the newly developed Attune and Stimulate Mother-Infant 56-items Checklist (A&S M-I) in two separate samples: one with infants with VI (N=20) and one with typically sighted (TS) infants (N=24). In addition, we assessed the contribution of parental sensitivity to attunement in dyadic interactions. The A&S M-I is an observational comprehensive checklist of behaviours that captures different body parts and their motility (i.e. finger movements, arm waving, foot kicking), and different senses (i.e. audio, tactile, visual). The appropriate responding of a parent to the child’s signal (i.e. matching, containing) reflects the ability to attune in the dyad as well as parent’s ability to stimulate the child to become engaged in the contact or activity. Consistency assessments revealed good reliability for maternal and infant behaviours, acceptable internal consistency and good test-retest reliability. Furthermore, both samples scored significantly above chance level on attunement, suggesting that the instrument captures parent-infant behavioral coordination, and VI was not related to parent-infant attunement. Lastly, a relation between parental sensitivity and attunement was found in the TS sample. Altogether, these findings provide promising initial evidence of the applicability of the A&S M-I checklist for assessing dyadic attunement across different populations and ages. Having assessed the applicability of this observational instrument, future work should corroborate these findings in larger samples.